Down syndrome - Tocci, Salvatore (New York : Franklin Watts, 2000)
Presents the disorder known as Down Syndrome, covering such aspects as historical background, medical causes, physical and mental limitations, and development from infancy through adulthood, including sexuality, social skills, and group homes.
Includes bibliographical references (p. 135) and index.
Keywords: Down syndrome -- Juvenile literature; Mental retardation -- Juvenile literature; Down syndrome; People with mental disabilities